Political Disinformation And Election Law Regulations In The Social Media Era - Hasugian, Marudut (Ipso Jure, 2025)
Political disinformation on social media has emerged as a major threat to electoral integrity due to its rapid, large-scale dissemination driven by platform algorithms. This study analyzes the patterns of political disinformation and evaluates the weaknesses of Indonesia’s electoral regulatory framework in addressing digital-era challenges. A Systematic Literature Review was conducted under the PRISMA protocol, selecting 14 peer-reviewed articles published between 2014 and 2024 and synthesizing them thematically. The findings reveal that political disinformation spreads through echo chambers, coordinated buzzer networks, AI-generated manipulative content, and interpersonal distribution in encrypted private channels. At the same time, Indonesia’s electoral regulations show structural limitations, including the absence of a clear legal definition of political disinformation, insufficient digital monitoring authority for election supervisors, lack of rules on political microtargeting and voter data protection, and limited cooperation between regulators and global digital platforms. The study concludes that comprehensive reform is required, involving legal definitional updates, enhanced institutional technical capacity, increased transparency in digital political advertising, and the adoption of multilevel governance frameworks to manage cross-border platform dynamics. These insights provide a foundation for policymakers to develop an electoral regulatory system that is more responsive and resilient in the social media era